Plasmid Vectors and Molecular Building Blocks for the Development of Genetic Manipulation Tools for Trypanosoma cruzi - Bouvier, León Alberto (2013)
The post genomic era revealed the need for developing better performing, easier to use and more sophisticated genetic manipulation tools for the study of Trypanosoma cruzi, the etiological agent of Chagas disease. In this work a series of plasmids that allow genetic manipulation of this protozoan parasite were developed. First of all we focused on useful tools to establish selection strategies for different strains and which can be employed as expression vectors. On the other hand molecular building blocks in the form of diverse selectable markers, modifiable fluorescent protein and epitope-tag coding sequences were produced. Both types of modules were harboured in backbone molecules conceived to offer multiple construction and sub-cloning strategies. These can be used to confer new properties to already available genetic manipulation tools or as starting points for whole novel designs. The performance of each plasmid and building block was determined independently. For illustration purposes, some simple direct practical applications were conducted.